PENGARUH GAYA HIDUP DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIANTAS DI KONTER RUMAH WARNA ROYAL PLAZA SURABAYA - RAHMAWATI, JUNI (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
This research discuss about the effect of life style and brand image towards the buying decision bags in Rumah Warna counter at Royal Plaza Surabaya. The background of the study is the importance of bag which is a part of women fashion and lifestyle. Nowadays, the function of bag is not only for carrying women’s need but also to make perfect women’s appearance. Rumah warna is one of the famous brand that can fulfill women’s need.The purpose of this research is describing the effect of life style and brand image towards the buying decision bags in Rumah Warna counter at Royal Plaza Surabaya both simultant and partial way. This research is descriptive research that use quantitative approach. The data are taken from questionnaire, observation, interview and documentation. This reasearch is conducted in Rumah Warna counter at Royal Plaza Surabaya.The result of thi research is signification F = 0,000 < alpha (0,05), it means that there is a significant simultantly effect between life style and brand image towards choice of buying. Signification test t variabel X1 = 0,023< 0,05 and signification test t variabel X2 = 0,000< 0,05, it means that there is partial effect between life style and brand image towards buying decision. Adjusted R Square point result is 0,269 which is meant 26,9% of buying decision bag in Rumah Warna counter at Royal Plaza Surabaya affected by life style and brand image. Whereas 73,1% can be affected by other variabel. The conclusion of this research, there is a significant effect between life style and brand image towards the buying decision bags in Rumah Warna counter at Royal Plaza Surabaya. Keywords: Lifestyle, Brand Image, Buying Decision